Effectiveness of Maintenance and Inspection Process using Augmented Reality Application - Abdul Aziz, Faieza; Alostad, Eisa; Arifin Ahmad, Kamarul; Sulaiman, Shamsuddin; Chun Hoe, Ooi (International Journal of Engineering and Technology, 2018)
Augmented reality is the integration of digital information and userâ€™s real life environment. It overlays virtual information on top of existing environment to userâ€™s perception towards the reality. Technicians and engineers in automotive industry at workshops today have mountains of data and information for diagnostics and repair. The worker must search for the information, and then manually check to see if he can assess the problem and repair what is not functional. Worker must refer to a printed drawing of the testing body, with the inspection parts marked on this drawing. Augmented reality application is proposed to replace these conventional references to eliminate their disadvantages. The objectives of this paper are to develop an augmented reality applicationto and evaluate the effectiveness of augmented reality application developed. Vuforia, Blender and Unity were used to develop augmented reality application due to their easy to use features. The application developed will be tested by respondents to conduct inspection and maintenance process using both conventional references and augmented reality application developed. Survey will also be carried out to evaluate the acceptance level of locals towards augmented reality application as well. The technology has proven to be popular in the automotive industry.Â Â